(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Electric-powered fixed-wing reconnaissance unmanned aerial vehicles (UAVs) have gained significant attention due to their efficiency, low acoustic signature, environmental friendliness, and operational flexibility. This article analyzes the constructive advantages of electric propulsion systems in fixed-wing reconnaissance drones, focusing on aerodynamic efficiency, structural simplicity, energy utilization, stealth characteristics, maintenance requirements, and mission adaptability. The study highlights how electric propulsion enhances endurance, reliability, and suitability for modern intelligence, surveillance, and reconnaissance (ISR) missions. Comparative analysis with internal combustion engine-based UAVs demonstrates that electric fixed-wing platforms provide superior performance in tactical and strategic reconnaissance applications.